2014
DOI: 10.1038/nature13270
|View full text |Cite
|
Sign up to set email alerts
|

Metformin suppresses gluconeogenesis by inhibiting mitochondrial glycerophosphate dehydrogenase

Abstract: Metformin is considered to be one of the most effective therapeutics for the treatment of type 2 diabetes (T2D) since it specifically reduces hepatic gluconeogenesis without increasing insulin secretion, inducing weight gain, or posing a risk of hypoglycemia1,2. For over half a century, this agent has been prescribed to T2D patients worldwide, yet the underlying mechanism by which metformin inhibits hepatic gluconeogenesis remains unknown. Here we show that metformin non-competitively inhibits the redox shuttl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
974
7
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,076 publications
(1,059 citation statements)
references
References 34 publications
32
974
7
16
Order By: Relevance
“…However, our study does not exclude that the glucose-lowering effect of metformin in patients with type 2 diabetes is mainly due to inhibition of HGP, e.g. by blocking glucagon-dependent hepatic glucose output [7,8]. In patients with type 2 diabetes this could involve increased circulating glucagon levels and enhanced hepatic sensitivity to glucagon, which is believed to contribute to an elevated HGP [27][28][29].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…However, our study does not exclude that the glucose-lowering effect of metformin in patients with type 2 diabetes is mainly due to inhibition of HGP, e.g. by blocking glucagon-dependent hepatic glucose output [7,8]. In patients with type 2 diabetes this could involve increased circulating glucagon levels and enhanced hepatic sensitivity to glucagon, which is believed to contribute to an elevated HGP [27][28][29].…”
Section: Discussionmentioning
confidence: 77%
“…The latter has been shown to abrogate activation of protein kinase A and by this mechanism antagonise glucagon-dependent glucose output in hepatocytes in mice [7]. Most recently, it was reported that metformin suppresses gluconeogenesis by inhibiting the hepatic redox shuttle enzyme mitochondrial glycerophosphate dehydrogenase (mGPD) in rodents [8]. Thus, metformin indirectly decreases the substrate fluxes of lactate and glycerol to the gluconeogenesis and the flux of electrons to the mitochondrial respiratory chain [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin enhances insulin sensitivity and lowers blood glucose levels by inhibiting gluconeogenesis in the liver. Metformin elicits these effects by inhibiting the mitochondrial respiratory‐chain complex I and glycerophosphate dehydrogenase (mGPD) and also by activating adenosine monophosphate‐activated protein kinase (AMPK) (Foretz et al ., 2014; Madiraju et al ., 2014). Activation of AMPK, in turn, leads to a plethora of signaling cascades that regulate energy homeostasis and metabolism (Hardie et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al reported a suppressing effect of hepatic glucagon signaling via inhibition of adenylyl cyclase activity that participates in metformin action [11]. Madiraju et al reported that metformin inhibits mitochondrial glycerophosphate dehydrogenase (mGPD), a glycerophosphate shuttle enzyme, to exert a suppressing effect on hepatic gluconeogenesis [12].…”
mentioning
confidence: 99%